Allegory of Wavering Faith: Renaming the Law and Gospel (1535) by Georg Lemberger in Light of the Lutheran Ministry of Consolation in Sixteenth-Century Germany - Han, Yu Na (Renaissance and Reformation / Renaissance et Réforme, 2025)
A painting by Georg Lemberger (c. 1490–1540) dated 1535 and housed in the Germanisches Nationalmuseum in Nuremberg presents a conspicuous variation of the representative Lutheran iconography, the Law and Gospel. The quintessential composition is delineated by the juxtaposition of scenes from the Old and New Testaments set against an unembellished backdrop. In Lemberger’s artistic rendition, however, the positions of the two testaments are inverted and accompanied by a tumultuous landscape in the background. The depictions of the Law and Gospel were conceived as an allegorical representation of faith, elucidating Luther’s doctrine of justificatio sola fide and imparting assurance to observers regarding their individual salvation. In contrast, Lemberger’s revised version portrays human frailty easily falling back into doubts and uncertainty about God and redemption. By giving a visual form to the negative experience the faithful would generally share, the image reminds viewers that they are not alone in such suffering and wondering.